An Autologous Dendritic Cell Vaccine Promotes Anticancer Immunity in Patients with Ovarian Cancer with Low Mutational Burden and Cold Tumors - Fucikova, Jitka; Hensler, Michal; Kasikova, Lenka; Lanickova, Tereza; Pasulka, Josef; Rakova, Jana; Drozenova, Jana; Fredriksen, Tessa; Hraska, Marek; Hrnciarova, Tereza; Sochorova, Klara; Rozkova, Daniela; et al. (Clinical cancer research, 2022)
PURPOSE: The successful implementation of immune checkpoint inhibitors (ICI) in the clinical management of various solid tumors has raised considerable expectations for patients with epithelial ovarian carcinoma (EOC). However, EOC is poorly responsive to ICIs due to immunologic features including limited tumor mutational burden (TMB) and poor lymphocytic infiltration. An autologous dendritic cell (DC)-based vaccine (DCVAC) has recently been shown to be safe and to significantly improve progression-free survival (PFS) in a randomized phase II clinical trial enrolling patients with EOC (SOV01, NCT02107937). PATIENTS AND METHODS: We harnessed sequencing, flow cytometry, multispectral immunofluorescence microscopy, and IHC to analyze (pretreatment) tumor and (pretreatment and posttreatment) peripheral blood samples from 82 patients enrolled in SOV01, with the aim of identifying immunologic biomarkers that would improve the clinical management of patients with EOC treated with DCVAC. RESULTS: Although higher-than-median TMB and abundant CD8+ T-cell infiltration were associated with superior clinical benefits in patients with EOC receiving standard-of-care chemotherapy, the same did not hold true in women receiving DCVAC. Conversely, superior clinical responses to DCVAC were observed in patients with lower-than-median TMB and scarce CD8+ T-cell infiltration. Such responses were accompanied by signs of improved effector functions and tumor-specific cytotoxicity in the peripheral blood. CONCLUSIONS: Our findings suggest that while patients with highly infiltrated, "hot" EOCs benefit from chemotherapy, women with "cold" EOCs may instead require DC-based vaccination to jumpstart clinically relevant anticancer immune responses.
Keywords: mutace; dendritické buňky; Cancer Vaccines; protinádorové vakcíny; nádory vaječníků; Biomarkers, Tumor; Carcinoma, Ovarian Epithelial; lidé; Female; nádorové biomarkery; epiteliální ovariální karcinom; Ovarian Neoplasms; Mutation; ženské pohlaví; Dendritic Cells; Humans